2021
DOI: 10.1155/2021/7849623
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultrasound-Guided Serratus Anterior Plane Block for Postoperative Analgesia in Patients Undergoing Breast Surgery: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: Objective. Serratus anterior plane block (SAPB) provides effective thoracic analgesia. This systematic review and meta-analysis was conducted to assess the safety and efficacy of SAPB for postoperative analgesia after breast surgery. Methods. A systematic literature search was performed using Embase, PubMed, Web of Science, and the Cochrane Library for eligible randomised controlled trials. The primary outcomes involved the administration of intraoperative and postoperative opioids. The Grading of Recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The results also showed that SAPB can reduce postoperative pain scores and opioid consumption at 24 h after surgery, and reduce the incidence of PONV after surgery. Regarding breast surgery, a meta-analysis by Hu et al showed that SAPB can reduce opioid consumption, relieve pain after breast surgery, and decrease the incidence of PONV to a certain extent [53,59]. Although the above studies have shown that SAPB can produce certain analgesic effects in different types of surgery, due to the prevalence of thoracic and breast surgery and the high heterogeneity between studies, it is necessary to further consider the effect of SAPB on postoperative pain in different types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that SAPB can reduce postoperative pain scores and opioid consumption at 24 h after surgery, and reduce the incidence of PONV after surgery. Regarding breast surgery, a meta-analysis by Hu et al showed that SAPB can reduce opioid consumption, relieve pain after breast surgery, and decrease the incidence of PONV to a certain extent [53,59]. Although the above studies have shown that SAPB can produce certain analgesic effects in different types of surgery, due to the prevalence of thoracic and breast surgery and the high heterogeneity between studies, it is necessary to further consider the effect of SAPB on postoperative pain in different types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic diffuses throughout this potential space, anesthetizing the anterolateral thoracic cage and upper abdominal wall. Similar to PECS blocks, the SAPB is safe and effective for pain management after chest wall surgeries and lateral rib fractures [21,28,[59][60][61][62][63]. Other painful conditions that have been successfully managed with this block in the ED include chest wall burns, intractable pain from herpes zoster, and placement of chest tubes [22,63].…”
Section: Trunkmentioning
confidence: 99%
“…Currently, there are various nerve block analgesia methods for post-operative patients who undergo breast removal (Hu et al, 2021). Paravertebral nerve block, serratus anterior plane block, modified serratus anterior plane block, pectoral nerve block I (Pecs I), modified pectoral nerve block II (Pecs II), transverse thoracic muscle plane blocks (TTMPB) and serratus-intercostal plane block (SIPB) can all be applied as post-operative analgesia for breast removal (Abdallah et al, 2021;Albi-Feldzer et al, 2021;Gabriel et al, 2021;Shi et al, 2021); they can all reduce post-operative pain in patients, decrease opioid consumption during and after surgery and enhance the quality of post-operative recovery to some extent (Albi-Feldzer et al, 2021;Hu et al, 2021;Mazzinari et al, 2019;Xiao et al, 2021). However, there is no conclusive evidence to prove the best nerve block analgesia method for breast cancer removal (Albi-Feldzer et al, 2021;Singh et al, 2022;Stokes et al, 2022), and the effect of different methods on the quality of post-operative recovery is unclear.…”
Section: Introductionmentioning
confidence: 99%